The past, present, and future of China-related accounting research - Cheng, Qiang; Hail, Luzi; Yu, Gwen (Journal of Accounting and Economics, 2022)
This discussion makes several observations regarding the past 25 years of China-related accounting research reviewed in Lennox and Wu (2022). First, we discuss factors of supply and demand that led to the rise of China-related studies and how this growth has contributed to the internationalization of accounting research. We note that the taxonomy of the literature by geographic region rather than topic or methodology is unusual and makes it difficult to formulate a common framework that would help organize the many contributions. Next, we distill distinct patterns in authorship, choice of topics, and asserted contributions of China-related studies. Studies are increasingly shaped by the availability of new data and regulatory reforms. These features should be interpreted carefully, as most reforms are interconnected and reflect the purposeful outcome of a tightly controlled economy. As a result, issues of generalizability arise. Alternatively, researchers could embrace the China setting and strive to identify the local institutional forces that make it special. We see such a more institutional, context-specific view of China-related—or better—international research as an opportunity for the field. We close by presenting five broad themes we view as promising areas for future China-related research.